Marketing intelligence. part a : understanding customers in the era of digitalization - Sinha, Mudita; Bhandari, Arabinda; Priya, Samant Shant; Kabiraj, Sajal (Emerald Publishing Limited, 2025)
In the fast-paced world of digitalization, understanding customers has never been more criticalor more challenging. Marketing Intelligence, Part A: Understanding Customers in the Era of Digitalization takes readers on a journey through the latest advancements in AI, data management, and digital channels that are reshaping the landscape of customer engagement and business strategy. This book explores the transformative power of Artificial Intelligence in enhancing customer experiences, from biometric analysis and Artificial Neural Networks (ANNs) to the ethical implications of AI in marketing. Uncover the dynamic relationship between markets and mobile applications, the role of experience orientation in service industries, and the promise of frictionless shopping in the digital age. With a special focus on centralized knowledge management in healthcare, the Internet of Things (IoT), and the growing importance of natural language processing in marketing intelligence, this comprehensive guide also delves into the ethical concerns surrounding AI adoption, as exemplified by a case study on Google AI. Whether you're navigating the complexities of digital channels to boost brand visibility or leveraging AI to create value for your customers, Marketing Intelligence, Part A: Understanding Customers in the Era of Digitalization provides the insights and strategies needed to thrive in today's digital marketplace. Perfect for marketers, business leaders, and technologists, this book equips you with the tools to understand and engage with your customers in the most effective and ethical ways possible.